Commemoration of Durruti. Rueda is speaking. Behind him , f.l.t.r: Domenech, ?, Puig Elias. Copied from CNT collection
Commemoration of Durruti. Rueda is speaking. Behind him , f.l.t.r: Domenech, ?, Puig Elias. Copied from CNT collection.